2016
DOI: 10.1016/j.egja.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation between ascorbic acid and N-acetyl cysteine for preventing tourniquet induced ischaemic reperfusion injury during lower limb surgery, a randomized controlled trial

Abstract: Tamer Yosef Hamawy (2016) Comparative evaluation between ascorbic acid and N-acetyl cysteine for preventing tourniquet induced ischaemic reperfusion injury during lower limb surgery, a randomized controlled trial, Egyptian

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Only two studies conducted on patients with hepatic resections led to significant outcomes (Donadon et al, 2016; Sayed et al, 2017). In comparison, none of the other studies conducted on patients and healthy subjects found that NAC administration significantly altered lactate levels (Agusti et al, 1997; Ammar & Abdou, 2020; Bailey et al, 2011; Christensen & Bangsbo, 2019; Erturk et al, 2009; Kelly et al, 2009; Laisalmi‐Kokki et al, 2009; Leelarungrayub et al, 2011; Mohamed & Hamawy, 2016; Nielsen et al, 2001; Orban et al, 2006; Peake et al, 1996; Shafiei et al, 2018; Spapen et al, 1998; Steib et al, 1998; Steib et al, 2013; Trewin et al, 2013; Walsh et al, 1998). Although, we are aware of an in vivo study implemented by Monti et al proposing that oxidative stress induces the expression of monocarboxylate transporter 4 (MCT4) in stromal cells, which is also known as an exporter of glycolytic byproducts such as pyruvate and lactate.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Only two studies conducted on patients with hepatic resections led to significant outcomes (Donadon et al, 2016; Sayed et al, 2017). In comparison, none of the other studies conducted on patients and healthy subjects found that NAC administration significantly altered lactate levels (Agusti et al, 1997; Ammar & Abdou, 2020; Bailey et al, 2011; Christensen & Bangsbo, 2019; Erturk et al, 2009; Kelly et al, 2009; Laisalmi‐Kokki et al, 2009; Leelarungrayub et al, 2011; Mohamed & Hamawy, 2016; Nielsen et al, 2001; Orban et al, 2006; Peake et al, 1996; Shafiei et al, 2018; Spapen et al, 1998; Steib et al, 1998; Steib et al, 2013; Trewin et al, 2013; Walsh et al, 1998). Although, we are aware of an in vivo study implemented by Monti et al proposing that oxidative stress induces the expression of monocarboxylate transporter 4 (MCT4) in stromal cells, which is also known as an exporter of glycolytic byproducts such as pyruvate and lactate.…”
Section: Discussionmentioning
confidence: 91%
“…In terms of gender distribution, 13 trials were conducted solely on male individuals (Bailey et al, 2011; Christensen & Bangsbo, 2019; Cobley et al, 2011; Kelly et al, 2009; Kerksick et al, 2010; Leelarungrayub et al, 2011; Michailidis et al, 2013; Nielsen et al, 2001; Orhan et al, 2006; Sakelliou et al, 2016; Sharma et al, 2017; Trewin et al, 2013; Zembron‐Lacny et al, 2009), whereas others were conducted on both genders. We categorized the study population into the following three groups: 25 studies on the patient (Agusti et al, 1997; Aliakbarian et al, 2017; Ammar & Abdou, 2020; Ayfer Aytemur et al, 2015; Donadon et al, 2016; Erdil et al, 2016; Erturk et al, 2009; Köksal et al, 2008; Kurian & Paddikkala, 2010; Laisalmi‐Kokki et al, 2009; Mahmoud & Ammar, 2011; Mohamed & Hamawy, 2016; Orban et al, 2006; Orhan et al, 2006; Peake et al, 1996; Peker et al, 2008; Rank et al, 2000; Sayed et al, 2017; Shafiei et al, 2018; Sharma et al, 2017; Song et al, 2015; Spapen et al, 1998; Steib et al, 1998; Steib et al, 2013; Walsh et al, 1998), 9 on trained (Christensen & Bangsbo, 2019; Cobley et al, 2011; Crum et al, 2018; Kelly et al, 2009; Kerksick et al, 2010; Michailidis et al, 2013; Nielsen et al, 2001; Trewin et al, 2013; Zembron‐Lacny et al, 2009), and 3 on healthy subjects (Bailey et al, 2011; Leelarungrayub et al, 2011; Sakelliou et al, 2016). Concerning the NAC administration form, 21 studies used the infusion form of NAC, and 16 others administr...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mohamed et al studied the impact of perioperative intravenous administration of vitamin C and N-acetylcysteine on the production of malondialdehyde, IL-6, and IL-8 as markers for oxidative stress and systemic inflammation in patients needing a tourniquet during surgery; the study included 60 patients who had undergone surgical intervention of the upper limb and received 1 g of vitamin C and 10 mg/kg N-acetyl cysteine. Following statistical analysis, there was an increased expression of IL-6, IL-8, and malondialdehyde in patients who had not received antioxidant substances [ 231 ]. Rumelin et al studied the plasmatic concentration of vitamin C in the pre- and postoperative period following the administration of 1 g of single-dose vitamin C. For the study, the authors divided the patients into two groups: one group that received 1000 mg vitamin C preoperatively and one group that received a placebo.…”
Section: Perioperative Antioxidant Therapymentioning
confidence: 99%
“…Regarding NAC, it is a direct precursor to glutathione (GSH) which directly scavenges ROS and indirectly supports GSH peroxidase [ 59 ]. The beneficial effect of NAC on TQ-related I/R injury has been reported [ 60 , 61 ]. However, a high dose of NAC significantly increased urine markers indicating renal tubular damage [ 30 ].…”
Section: Effects Of Pharmacological Intervention On Tq-induced I/rmentioning
confidence: 99%